Use Coupon: CART20 and get 20% off on all online Study Material

Total Price: R

There are no items in this cart.
Continue Shopping
Get instant 20% OFF on Online Material.
coupon code: MOB20 | View Course list

Get extra R 350 off


actullaly i am not able to understand what is homozenizing a pair of line

what do we get after homogenizing


5 years ago


Answers : (1)


After the homogenisation of the pair of straight lines we get a combined equation of the two lines from the origin. It helps in solving many complex problems  

5 years ago

Post Your Answer

Other Related Questions on Analytical Geometry

equations of lines which passes through the points of intersection of the lines 4x-3y-1=0and 2x-5y+3=0and are equally inclined to the axes are: y(+or-)x=0 y-1=(+or-)1(x-1) x-1=(+or-)2(y-1)...
The Point of intersection is (1, 1) The equation of line passing through this point is y-1 = m(x-1) where m is slope or y-mx + m-1 = 0. Since line makes equal with both axes this is...
Ajay 2 months ago
If a+b+c=0,then the family of lines 3ax + by + 2c = 0 pass through the fixed point
Dividing the whole eqn. by 2 and comparing with a+b+c = 0 3ax + by + 2c = 0 we get, 3a/2 x + b/2 y + c = 0 3x/2 = 1 x = 2/3 and y/2 = 1 y = 2. hence (x,y) that is (2/3 , 2) is the fixed...
2017 years ago
Find equation to the tangent at A to the circle (x-a)^2 + (y-b)^2 =r^2 where the radius through A makes an angle alpha with the x axis.
The Co-ordinates of center are (a,b) and radius is r. Since radius to A makes angle with x axis the co-ordinates of A are (a + rcos , b+rsin ). Now we know A its easy to find equation of...
Ajay 2 months ago
dfine scalar product .give itsproperties and tow examples tell fast brows
Dear Sreekanth Indla, Scalar product of two vectors is defined as the product of the magnitudes of the two vectors and cosine of the angle between them.
SAI SARDAR 7 months ago
find the sum of the given series. description given in the image
Harsh Patodia one month ago
(r 2 +1) . r! = (r 2 +2r+1).r! -2r.r! = (r+1) 2 r! – 2r.r! = (r+1) (r+1)r! – 2r.r! = (r+1).(r+1)! – r.r! – r.r! =[(r+1).(r+1)! – r.r!] – [(r+1)! – r!] Thus, the summation is seen to be sum...
mycroft holmes one month ago
View all Questions »

  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details
Get extra R 3,750 off

Get extra R 350 off

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts

Post Question

Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details